The institutionalization of the alpine region: an analysis based on a study of two pan-alpine networks (Alliance in the Alps and Alparc) - Cristina Del Biaggio (Revue de Géographie Alpine)
This article attempts to show, through an analysis of two pan-alpine networks, Alliance in the Alps and Alparc, how the Alps are in the process of becoming institutionalized and emerging as a transnational region. This endeavour requires above all an understanding of how these networks function as well as an appreciation of the major challenges facing those involved in projects in this innovative process. The process is taking place at the scale of the entire alpine arc and is contributing to recognition of the Alps as a region in its own right in the European territorial mosaic.